FUNGSI KAWASAN DAN STRATEGI PENGELOLAAN HUTAN LINDUNG WOSI RENDANI KABUPATEN MANOKWARI - Anton Silas Sinery dan Mahmud (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
The results of the research showed that the forest of Wosi Rendani protection has slope 21.9% (score 60), soil type podsolic/ ultisol (Score 60) and 12.86 rain intensity (score 10), altitude 210 m asl,  with a total score of 130 as a buffer zone.  Perceptions of respondents unanimously positive 64.17% and 75% attitude towards local community-based management. This is due to the location of protected areas that are near human settlements and local immigrant who feared if the protected forest next to landslides and people lack of clean water.  Inside the forest, there is an object HLWR areas and attractions such as waterfalls, caves, springs, pools that can be used as the establishment of protected forest.  Protected forest of Rendani Wosi area has considerable potential to support regional management efforts such as the potential for flora and fauna, water, waterfalls and springs and caves as well as the support of the community around the area, but the legality of the area there has been no major obstacles in the management of this protected forest